Iš spaudos draudimo istorijos - Vėbra, Rimantas (Literatūra, 1974)
The letters published here are from the period of the ban of the Lithuanian press by czarism (1865-1904). They were written by the noted Lithuanian public men of that time J. Šliūpas, S. Baltramaitis, M. Dayvainis-Silvestraitis. The originals of the letters belong to the State Historical Archives in Leningrad. The facts and ideas expressed in the letters are of importance for any investigator of the history of that period. Besides, the letters add some new data to the public activities of the above-mentioned men.